Volunteers : growing up in the forever war - Alexander, Jerad W., 1980- (Algonquin Books of Chapel Hill, 2021)
"The memoir of a young man from a long line of enlisted men and women, raised on military bases and shaped from a young age to idolize and glorify war and the people who fight it. After he joins the Marines and serves in Iraq, he must begin to reckon with the troubled and complicated truths of the American war machine"--